Cell-mimicking nanolipogel for encapsulation and delivery of hydrophilic biomolecules - Liew, Melvin Wen Jie (Nanyang Technological University, 2023)
High initial burst release of hydrophilic biomolecules is just one of the many challenges faced by lipid based nanoparticulate formulations, even though it is widely used for drug encapsulation and delivery studies. One of the emerging potential strategies is the use of nanolipogels (NLG) to encapsulate hydrophilic drugs, which have the ability to suppress the initial burst release. This gives a level of control and sustain to the release of hydrophilic drugs. However, current works are short on characterisation of the mechanism for the release from NLG systems. Therefore, in this work, varying molecular weight of Poly (ethylene glycol) Diacrylate (PEGDA) (575 Da, 2000 Da, 4000 Da) were used for the fabrication of PEGDA NLG of varying mesh sizes of the nanogel cores, to study the mechanism for release of Dextran-Fluorescein Isothiocyanate (DFITC). Macromolecular crowding effects in cells provided the inspiration for the work, when looked at as a polymeric network with varying mesh sizes. Fluorescence Recovery after Photobleaching (FRAP), were performed on cell derived microlipogels (MLG), a novel system developed as a solution to limitations of FRAP, to provide a further mechanistic study and characterization of the diffusion and release of encapsulated biomolecule from the nanogel core. Results from the studies has shown that the NLGs’ mesh sizes are controllable via the use of different Mw of PEGDA, where a lower Mw used resulted in a smaller mesh size of the nanogel core, by having a higher crosslinking density. This in turn, gave higher suppression of the initial burst release of DFITC, up to a 10-fold difference for crosslinked PEGDA 575 NLGs, as compared to bare liposomes. FRAP results then gave further validation by showing that the smaller mesh size restricted the diffusion of DFITC, consequential of a lower mobile fraction. These gave clear insight into the possibility of controlling the encapsulation and release of hydrophilic biomolecules, by targeting the fabrication of nanogel core. From this, Chitosan Methacrylate (CMA) NLGs was then studied to expand into other ways in manipulating the nanogel core for greater control, such as a differently charged core. Results was shown that CMA NLGs are also able to suppress the initial burst release of DFITC and it can be controlled by using a different concentration of CMA for the fabrication of nanogel core, where higher concentrations used results in greater suppression. This increases the possible strategies for consideration during the design of NLG systems and especially CMA NLGs opens up the possibility of encapsulation of negatively charge biomolecules, such as siRNA. As the NLG system involves two critical components, namely the nanogel core and the bilayer coating, the membrane properties are also essential during the designing of a NLGs. Herein, cell membrane coating for NLG was studied. As cell membranes are almost 50% made up of proteins in mass which gives majority of membrane properties, preservation of these protein during the coating of nanoparticles will possibly confer the membrane properties, such as prolonged in-vivo circulation and improved cellular uptake, onto the nanoparticles. This was proven through flow cytometry that the characteristic membrane proteins of cell derived nanovesicles (CDN), namely CD9, CD81, TSG101, and of RBC membrane vesicles, CD47, were all present on the nanoparticles surfaces. RBC coated nanoparticles were also shown that it can further suppress the initial burst release and sustained release, as compared to L-α-phosphatidylcholine (Egg, Chicken) (EPC) NLGs. Furthermore, a novel approach for coating using microfluidics, was proven to be successful in coating the nanoparticles with CDNs. This sure opens up opportunities for increased throughput and automation of the coating process in future works. All in all, it was shown that cell mimicking NLG system was able to provide a controlled release of hydrophilic biomolecule, and the release mechanism was studied and characterized using FRAP. Relationships with changes to the nanogel core as well as membrane coatings were also explored and proven to be viable and plausible expansions to other membrane origins were discovered. This work has provided a guide on the design of NLGs for a multitude of needs with regards to encapsulation and delivery, as well as in vivo performance.